SMOKING STATUS AND EFFECTIVENESS OF ANTIHYPERTENSIVE VASODILATING - O. V. Fedorishina; K. V. Protasov; A. A. Dzizinskyi (Кардиоваскулярная терапия и профилактика, 2013)
Aim. To compare antihypertensive effectiveness of carvedilol, nebivolol, and amlodipine in smokers and non-smokers with arterial hypertension (AH).Material and methods. The study included 130 patients with Stage 1–2 AH, aged 30–55 years, who were randomised into three treatment groups: carvedilol (n=56), nebivolol (n=44), and amlodipine (n=30). Each group was also divided into two subgroups of smokers and nonsmokers (never-smokers or ex-smokers who stopped smoking at least one year ago). At baseline and after 8 weeks of the treatment, the dynamics of office blood pressure (BP) levels, parameters of 24-hour BP monitoring, and lung function were compared across the subgroups.Results. After 8 weeks of the treatment, office BP levels reduced significantly and comparably in all subgroups. According to the results of 24-hour BP monitoring, smokers from the carvedilol group did not demonstrate any marked BP dynamics, in contrast to their non-smoking peers. Smokers treated with nebivolol demonstrated no reduction in mean 24-hour levels of systolic BP (SBP), with some reduction in mean 24-hour and mean daytime levels of diastolic BP (DBP), as well as a decrease in SBP and DBP variability. Amlodipine effectively reduced mean 24-hour BP levels in both smokers (by 10,0/8,0 mm Hg) and non-smokers (by 11,3/6,5 mm Hg), with similar dynamics of mean daytime SBP and DBP and mean nighttime SBP. Lung function parameters in smokers receiving amlodipine did not change, while the β-adrenoblocker treatment negatively affected these parameters in smokers. In the carvedilol group, smokers demonstrated a significant reduction in FEV1; in the nebivolol group, FEV1, FLC, and their ratio significantly decreased in smokers.Conclusion. In young and middle-aged smokers with AH, antihypertensive effects, as assessed with the 24-hour BP monitoring, were weaker for carvedilol (SBP and DBP) and nebivolol (DBP). Amlodipine was highly effective in both smokers and non-smokers. Therefore, amlodipine could be recommended as one of the first-choice medications for smoking patients with AH.